2018
DOI: 10.1016/j.sjbs.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

High-efficient extraction of principal medicinal components from fresh Phellodendron bark (cortex phellodendri)

Abstract: The hydrochloric acid/methanol-ultrasonic extraction has the best effect for three medicinal components of fresh bark, providing an extraction yield of 103.12 mg/g berberine, 24.41 mg/g phellodendrine, 1.25 mg/g palmatine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
2
22
0
2
Order By: Relevance
“…When leaves of O. Fragrance were under high temperature stress, ADH gene expression would be increased because of the resistance response mechanism activation in order to avoid from heat damage. Many researches about functional components in the leaves, flowers (Ge et al, 2018a and2018b), barks (Ge et al, 2017a and, stems (Ge et al, 2017c and2017d), roots (Ge et al, 2017e;, fruits (Jiang et al, 2018a and2018b), timbers (Peng et al, 2017a and and byproducts (Liu et al, 2017;Xie et al, 2018) of plants showed that they contain many bioactive components (Peng et al, 2016;He et al, 2017;Cheng et al, 2017;Yang et al, 2017;Qin et al, 2017;Xu et al, 2018;Wang et al, 2018). This result was consistent with the resistance response function of ADH (Strommer et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…When leaves of O. Fragrance were under high temperature stress, ADH gene expression would be increased because of the resistance response mechanism activation in order to avoid from heat damage. Many researches about functional components in the leaves, flowers (Ge et al, 2018a and2018b), barks (Ge et al, 2017a and, stems (Ge et al, 2017c and2017d), roots (Ge et al, 2017e;, fruits (Jiang et al, 2018a and2018b), timbers (Peng et al, 2017a and and byproducts (Liu et al, 2017;Xie et al, 2018) of plants showed that they contain many bioactive components (Peng et al, 2016;He et al, 2017;Cheng et al, 2017;Yang et al, 2017;Qin et al, 2017;Xu et al, 2018;Wang et al, 2018). This result was consistent with the resistance response function of ADH (Strommer et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…FA was applied to quantify alkaloids in different parts of eight Berberis species [11] while TFA was added into both double‐distilled water and acetonitrile (ACN) for determination of palmatine from barks of Phellodendron amurense Rupr. or P. chinense Schneid [12]. Mobile phase system containing FA, methanol, and water was employed in the analysis of amaryllidaceae alkaloids from herbs of Narcissus tazetta L. [13].…”
Section: Chromatographic Separation Methodsmentioning
confidence: 99%
“…SDS was also employed to determine phellodendrine and berberine from barks of Phellodendron amurense Rupr. or P. chinense Schneid [12]. Quality assessment of isoquinoline alkaloids in herbs of Corydalis impatiens (Pall.)…”
Section: Chromatographic Separation Methodsmentioning
confidence: 99%
“…Some bioactive components were found in benzene extracts which can be used in spices and food additives. Hexadecanoic acid, ethyl ester for perfume flavor, Octadecanoic acid, ethyl ester are mainly used for the preparation of bacon flavor [32][33][34]. Tetradecanoic acid is the raw material of spices.…”
Section: Comparison Of Volatile Components In Two Extractsmentioning
confidence: 99%